Models of Modern Capitalism: A Comparative Institutional Analysis - ШевчукАндрей Вячеславович (Journal of Economic Sociology, 2010)
Economic systems of the developed societies, which traditionally are labeled ‘capitalist’ or ‘market’ ones, are ratherheterogeneous in reality. There are several independent economic models that differ in socio-economic, political andideological respects. The paper covers a range of methodological approaches to the comparative analysis of economicsystems, and sketches its basic typology comprising ‘liberal capitalism’ of Anglo-Saxon world and ‘non-liberalcapitalism’ of continental Europe, Japan and some other countries. Two models of capitalism are differentiated by thetype of economic agents and institutional setting. Each of them holds specific competitive advantages, which enablesthem more or less successfully to reduce socio-economic problems. Unfolding globalization does not implyconvergence and unification of economic practices. Rather hybridization takes place implying institutional changes thatenable economic models to meet the new challenges.